Mobile access to government information and services : trends and federal actions - Weaver, Jordan L. (Media and communications-- technologies, policies and challenges., 2015)
Today, millions of Americans use mobile devices like smartphones and tablet computers on a daily basis to communicate and obtain information. Further, due to recent technical advances in mobile technology, consumers can use these devices to carry out a broad range of activities that previously required a desktop or laptop computer including shopping, banking, and accessing government services. Given these trends, providing government information and services ""anytime, anywhere, and on any device, "" has become increasingly important, particularly as some mobile users may not have any other mea.